Solvent effects on the photophysical properties of Bu4N[(4,40-bpy) Re(CO)3(bpy-5,50-diCOO)] complex. A combined experimental and computational study - Martinez Saavedra, Hector H. (2016)
The photophysical properties of the complex Bu4N[(4,40-bpy)Re(CO)3(bpy-5,50-diCOO)] were studied inprotic and aprotic media with the aid of steady-state and time-resolved techniques and TD-DFT calculations.The absorption spectrum as well as the steady state and time resolved luminescence of the Re(I)complex display a marked solvent effect. The highest and lowest energy absorption bands experience abathochromic shift as the polarity of the solvent decreases. In addition, the lowest energy band broadens.Two luminescence bands were observed around 430 and 600 nm in protic organic solvents like alcohols.The high energy emission is observed solely in aqueous solutions, while in aprotic solvents only the lowenergy luminescence is detected. TD-DFT calculations allowed us to identify the main electronic transitionsin the low energy region as 1MLLCTReðCOÞ3/4;40 bpy and 1MLLCTReðCOÞ3/bpy 5;50 diCOO. The simulatedabsorption spectra of the Re(I) complex in H2O, protic (EtOH, MeOH) and aprotic (CHCl3, CH2Cl2,CH3CN) organic solvents follow the experimental absorption spectra with reasonable accuracy both inposition and relative intensities. The magnitude of the calculated dipole moment (m) increases with thedielectric constant of the solvent (εr). Besides, the energy of 1MLLCTReðCOÞ3/4;40 bpy also increases with εr.However, the energy of the 1MLLCTReðCOÞ3/bpy 5;50 diCOO transition is rather insensitive to εr. Thisdisparity is attributed to the fact that the 1MLLCTReðCOÞ3/4;40 bpy transition is nearly parallel to theorientation of m while the 1MLLCTReðCOÞ3/bpy 5;50 diCOO transition is almost perpendicular to it. UnrestrictedTD-DFT calculations were successfully applied to the triplet species. It is observed that in thetriplet state the ReeN distances are shortened while ReeC distances are elongated relative to the groundstate. The calculated emission energy by TD-DFT and/or D(SCF) methods was compared to the experimentalemission maximum in chloroform. All the experimental results as well as the theoretical calculationsindicate that solvent effects on the steady state and time resolved luminescence of the Re(I)complex can be accounted by the coexistence of 3MLLCTReðCOÞ3/4;40 bpy, 3MLLCTReðCOÞ3/bpy 5;50 diCOOand 1IL excited states Remove selected